Development of the University College Dublin hollow cylinder apparatus - O'Kelly, Brendan (My University, 2003)
Development of the University College Dublin hollow cylinder apparatus
Proceedings of the 56th Annual Canadian Geotechnical Conference
PUBLISHED
Winnipeg, Ontario
Keywords: hollow cylinder apparatus